AB0366 Clinical, epidemiological characterisictis and comorbidities in a cohort of paraguayan patients with rheumatoid arthritis. (12th June 2018) - Roman, L.; Riquelme-Granada, S.; Losanto, J.; Duarte, M.; Cabrera-Villalba, S.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic rheumatic inflammatory disease with a higher risk of developing some cardiovascular pathology compared to the general population. The presence of comorbidities in patients with RA represents an increase in the cost of care, work disability and hospital admissions. Objectives: To describe clinical, epidemiological characteristics, frequency of comorbidities and their association with clinical and analytical characteristics in Paraguayan patients with rheumatoid arthritis. Methods: Descriptive, cross-sectional study of a cohort of patients with established rheumatoid arthritis, followed in the Department of Rheumatology of the Hospital de Clínicas. epidemiological (i.e. sex, age, origin), clinical (i.e., comorbidities (i.e. HBP was defined as BP ≥140/90), obesity BMI ≥30, dyslipidemia according to lipid profile levels), time of evolution of the disease, DAS28, etc.), laboratorial (i.e. RF, anti-CCP) and radiographic variables were recorded. Qualitative variables were expressed in frequencies and percentages and quantitative variables were characterised by their means and standard deviations. The comparison of clinical, epidemiological, serological variables was performed using the chi-squared test and the student test respectively for qualitative and quantitative variables. The statistical analysis was performed with the statistical program SPSS V.23.0. Results: 177 patients with RA were included, 82.5% were women, with a mean of age at onset of 44.8±13.8 years, mean disease duration of 8.64±8.3 years. 68.3% came from Asunción and Gran Asunción, 44.6% of the patients were married, the average number of children per patient was 3.55±2.2. Most of the patients (43.6%) were from social stratum 1–2, according to the GRAFFAR questionnaire. Family income with minimum salary or less was found at 55, 7% of patients with an average household income of 2.350.515±1.6220.409 Guaranies. Most patients work at home, 54. 5% were housewife, and only 11.9% had a university degree. Only 15.3% had extra-articular manifestations, mainly rheumatoid nodules. The average body mass index was 29.6±12.7. 75, 9% were RF positive, with a mean of level of 436.7±301 UI/L and 85% were anti-CCP positive, with a mean of level of 224, 7±201 UI/L. Methotrexate was the most frequent treatment (87%), 57.7% were using prednisone, with a median dose of 7.9±4.8 mg. 40, 9% had erosions. In this cohort median disease activity was 3.5%±1.2. 30.7% of patients were in remission by DAS 28 (<2.6). Regarding comorbidities, 38% presented hypertension, 11.9% had dyslipidemia, 5.3% type-2 Diabetes Mellitus, 39.4% were obese and 35% were overweight. Only 5% were smoker, and 16.5% had osteoporosis. When comparing the presence or absence of comorbidities with the clinical, epidemiological, serological and radiological characteristics, we did not find significant differences between them. Conclusions: In this cohort of patients with established RA a little more than half receive a monthly income less than or equal to the minimum salary, and only the minority had university studies. The most frequent comorbidities were obesity, hypertension and dyslipidemia. One third of patients were in clinical remission, only with DMARDs. Disclosure of Interest: None declared